2004
DOI: 10.1016/s0002-9440(10)63761-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum-Infected Erythrocytes Adhere Both in the Intervillous Space and on the Villous Surface of Human Placenta by Binding to the Low-Sulfated Chondroitin Sulfate Proteoglycan Receptor

Abstract: In pregnant women infected with Plasmodium falciparum, the parasite-infected red blood cells (IRBCs) sequester in the placenta through chondroitin 4-sulfate (C4S)-mediated adherence. The pattern of IRBC adherence in P. falciparum-infected placenta has been controversial. Moreover, the identity of the chondroitin sulfate proteoglycan (CSPG) receptor, that mediates IRBC adherence, and its location in the placenta have not been established. This study, using immunohistochemical techniques, clearly shows, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 49 publications
3
80
2
2
Order By: Relevance
“…Particularly we showed that an unusually low sulfated CSPG localized predominantly in the intervillous space is the natural receptor for the placental IRBC adherence (14). Further we and others demonstrated that optimal IRBC binding requires the participation of both 4-sulfated and 4-nonsulfated disaccharide moieties (15)(16)(17)(18).…”
mentioning
confidence: 76%
“…Particularly we showed that an unusually low sulfated CSPG localized predominantly in the intervillous space is the natural receptor for the placental IRBC adherence (14). Further we and others demonstrated that optimal IRBC binding requires the participation of both 4-sulfated and 4-nonsulfated disaccharide moieties (15)(16)(17)(18).…”
mentioning
confidence: 76%
“…19 -21 A previous study from our laboratory has shown that a uniquely low-sulfated chondroitin sulfate proteoglycan (CSPG) mediates IRBC adherence, and that the CSPG is localized predominantly in the intervillous space and to a lesser extent on the surface of the syncytiotrophoblast cells. 22 We and others have also demonstrated that a dodecasaccharide motif of C4S consisting of two foursulfated and four-nonsulfated disaccharide moieties comprise the minimum motif for optimal IRBC binding. [23][24][25][26] Thus, C4S has been shown to be the receptor for placental IRBC adherence.…”
mentioning
confidence: 83%
“…22 The fixed tissues were transferred to ice-cold PBS and stored at 4°C. The tissues were paraffin-embedded, cut into 5-m-thick sections onto glass slides, deparaffinized with xylene, and rehydrated by sequential immersion in 100, 95, and 70% ethanol and then in Tris-buffered saline, pH 8.0 (TBS).…”
Section: Pieces (ϳ1 CMmentioning
confidence: 99%
See 2 more Smart Citations